(untitled) (Ahkam: Jurnal Hukum Islam, 2024)
One proof of the unique freedom of legal thought in the early days of Islam in the first Hijriah/7 AD and second Hijriah/8 AD centuries, was the emergence of a large collection of legal views that grew in various centers in Iraq, Hijaz, Syria and Egypt. One of them is the moderate Shafi’i school founded by Muhammad bin Idris Asy-Syafi’i. This research aims to describe the contextualization of Ash-Shafi’i legal events and thoughts regarding Qawl Qadim and Qawl Jadid, as well as to synthesize Ash-Shafi’i law when faced with different social conditions in society, while many legal cases have emerged that require solutions. law immediately. This research is in the form of qualitative descriptive research, using a literature review. The research objects of this research are writings and texts that describe and are related to this research using content analysis data processing methods from these writings. From the results of the analysis it was found that Ash-Shafi’i in carrying out legal synthesis, both in the context of Qawl Qadim and Qawl Jadid, did not only adhere to historical texts, but also used ra’yu, both of which were used in a balanced and parallel manner.